Neurosarcoidosis: overview of management and differentiation from fungal aetiologies - Shawn Khan; Khushi Saigal; Juan Varela; Gabriel Flambert; Parth Patel; Arman Mahmood; Brandon Lucke-Wold (Romanian Neurosurgery, 2024)
Neurosarcoidosis, a rare inflammatory condition, poses a diagnostic challenge due to its various clinical presentations and potential mimics. This comprehensive review delves into the complexities of neurosarcoidosis, emphasizing the importance of a thorough diagnostic workup and the consideration of alternative conditions, such as fungal mimics. The study explores the intricacies of the diagnostic process, particularly the role of histopathology, imaging, and laboratory tests. The current state of neurosarcoidosis management is examined, such as the use of corticosteroids as well as novel therapies including Rituximab and JAK-STAT inhibitors. The clinical spectrum is described in detail for both the peripheral and central nervous systems, offering insights into the many presentations, which include ocular manifestations and syndromes like Heerfordt's syndrome. The complexities of neurosarcoidosis necessitate further research in its diagnosis, pharmacotherapy, and management. The inclusion of information on ongoing research and clinical trials underscores the need for tailored therapeutic approaches.